Fluoroscopy Time Required for Each Step of Interventional Endoscopic Ultrasonography - Watanabe, Masafumi; Okuwaki, Kosuke; Kida, Mitsuhiro; Imaizumi, Hiroshi; Adachi, Kai; Tamaki, Akihiro; Hanaoka, Taro; Ogawa, Daisuke; Kusano, Chika (Journal of Digestive Endoscopy, 2025)
Interventional endoscopic ultrasonography (I-EUS) exposes patients to high levels of radiation exposure. However, no research on the fluoroscopy time required for each step of I-EUS has been published. That was the aim of this study.We retrospectively included patients who underwent endoscopic ultrasonography-guided biliary drainage (EUS-BD) and pancreatic duct drainage (EUS-PDD) in our hospital from October 2022 to November 2024. The procedure was categorized into four steps: step 1, transmural puncturing; step 2, guidewire placement; step 3, tract creation; and step 4, stent placement. We measured the fluoroscopy time required for each step via the fluoroscopic videos.Continuous variables were described using medians and the first to third quartiles (Q1–Q3).The study included 36 participants (EUS-BD: 33, EUS-PDD: 3). The median [Q1–Q3] fluoroscopy times required for steps 1 to 4 were 120 [96–152], 175 [123–449], 194 [101–303], and 171 [90–208] seconds, respectively, for EUS-BD and 169 [119–195], 302 [234–529], 435 [430–477], and 233 [170–266] seconds, respectively, for EUS-PDD.In I-EUS, the fluoroscopy time required for step 3, tract creation, was the longest. The technique needs to be improved, new devices developed, and clear communication be established among the operating team to prevent unnecessary fluoroscopy.
Keywords: fluoroscopy; interventional endoscopic ultrasonography; radiation exposure